(untitled) (Colombia Medica, 1993)
From January to March of 1988, the health status of children in 40 daycare centers of the Colombian Institute of Family Welfare in two neighborhoods (El Retiro and El Poblado I) in the Aguablanca district of Cali, Colombia, was assessed. In each, 20 centers were randomly chosen. For every child, a clinical history and physical examination were performed. Every third child was tested for CBC, reticulocytes, and sickle cell disease, and a stool sample was examined for ova and parasites. Average age of the children was 50 months. Twenty-five percent were undernourished, and 22% were anemic (average Hb: 12 g/dl, range 6-14 g% ). Eosinophilia was detected in 50% (mean 2453/mm3), and 80% suffered polipara-sitism caused by Entamoeba histolytic and Giardia lamblia associated with Ascaris lumbricoides. Sickle cell disease was found in 9 children, as well as one infant, with a persistence of 45% of fetal hemoglobin.